2008
DOI: 10.1007/s11156-008-0090-y
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and financial performance: the “virtuous circle” revisited

Abstract: Corporate governance, Corporate culture, Social responsibility, G34, M14,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
313
5
30

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(374 citation statements)
references
References 13 publications
26
313
5
30
Order By: Relevance
“…However, our results are not consistent with previous studies that suggest CSR has a negative effect on performance [18,19]. Those studies also found no significant CSR-performance linkage [22,23]. The results mean that synergy of CSR could also be generated in M&A activities.…”
Section: Effects Of Csr On Long-term Manda Performancecontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our results are not consistent with previous studies that suggest CSR has a negative effect on performance [18,19]. Those studies also found no significant CSR-performance linkage [22,23]. The results mean that synergy of CSR could also be generated in M&A activities.…”
Section: Effects Of Csr On Long-term Manda Performancecontrasting
confidence: 99%
“…The results of empirical studies regarding the economic impacts of CSR are also mixed. Some studies have found no significant relationship between CSR and a firm's economic performance [22,23]. Other studies provide evidence of a significant relationship between CSR and corporate performance [24][25][26][27].…”
Section: Corporate Social Responsibility and Firm Performancementioning
confidence: 99%
“…To date, however, the direction of causality remains an open empirical question (Gray et al, 1995(Gray et al, , 2001Brammer & Pavelin, 2006. In our study, drawing upon Nelling & Webb's (2009) application of Granger causality, we explicitly test for causality between our sample firms' profitability and their E and S disclosures.…”
Section: Environmental and Social Disclosures And Profitabilitymentioning
confidence: 99%
“…The literature suggests that a "virtuous circle" exists, generated by a combination of the slack resources and good management approaches, which determines that increased CSP leads to improved financial performance and vice versa (Waddock and Graves, 1997a;Hillman and Keim, 2001;Nelling and Webb, 2009;Zhao and Murrell, 2016). The "virtuous circle" between CSP and CFP is tested in the banking sector, formulating the following research hypothesis:…”
Section: Hy2: the Bank's Financial Performance Positively Influences mentioning
confidence: 99%
“…In particular, the theoretical assumptions of the Stakeholder Theory are tested, in order to investigate the existence of an influence of CSP on financial performance (good management approach); at the same time, the effect of financial performance on the CSP is tested (slack resources approach). The final aim of the research is to identify whether both slack resource and good management theory may be operating simultaneously, constituting the existence of a "virtuous circle" between the two performance measures, in the European banking sector (Waddock and Graves, 1997a;Nelling and Webb, 2009). …”
mentioning
confidence: 99%